2018
DOI: 10.1136/bmjopen-2018-021800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on cognition and behaviour in children with neurofibromatosis type 1: a study protocol for a randomised placebo-controlled crossover trial

Abstract: IntroductionDopamine dysregulation has been identified as a key modulator of behavioural impairment in neurofibromatosis type 1 (NF1) and a potential therapeutic target. Preclinical research demonstrates reduced dopamine in the brains of genetically engineered NF1 mouse strains is associated with reduced spatial-learning and attentional dysfunction. Methylphenidate, a stimulant medication that increases dopaminergic and noradrenergic neurotransmission, rescued the behavioural and dopamine abnormalities. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…A year-long clinical study of children with NF1 found that the administration of the stimulant medication methylphenidate significantly improved cognitive and academic performance as well as social deficits [17]. Double-blind placebo-controlled crossover trials have demonstrated the efficacy of methylphenidate in reducing ADHD symptoms at four weeks [45] and cognitive symptoms at six weeks [46]. The efficacy of stimulants in patients with NF1 and ADHD has been theorized to relate to the predominance of the combined subtype in this population [47].…”
Section: Discussionmentioning
confidence: 99%
“…A year-long clinical study of children with NF1 found that the administration of the stimulant medication methylphenidate significantly improved cognitive and academic performance as well as social deficits [17]. Double-blind placebo-controlled crossover trials have demonstrated the efficacy of methylphenidate in reducing ADHD symptoms at four weeks [45] and cognitive symptoms at six weeks [46]. The efficacy of stimulants in patients with NF1 and ADHD has been theorized to relate to the predominance of the combined subtype in this population [47].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms responsible for such regulation are still unknown. Clinical trials conducted with methylphenidate showed an effect in the reduction of attention deficits, spatial working memory impairments, and ADHD symptoms in children with NF1 [121].…”
Section: Regulation Of Dopamine Levelsmentioning
confidence: 95%
“…Although preliminary clinical trials have demonstrated that methylphenidate is eff ective in treating ADHD symptoms in children with NF1, its therapeutic eff ect on cognitive performance is unclear. Currently an ongoing randomised, doubleblind, placebo-controlled trial to assess the effi cacy of methylphenidate for reducing att ention deficits, spatial working memory impairments and ADHD symptoms in children with NF1 is being conducted (44). The results of this trial will be published in the near future.…”
Section: Possibilities Of Medication Treatment Of Behavioural Impairmmentioning
confidence: 99%